Perancangan Interior Bengkel Body Repair Yuspeed di Surabaya dengan konsep âMoving Forwardâ - Poppy F. Nilasari, Billy Sugihono Martino Dwi Nugroho (Intra, 2014)
The growing number of cars in Indonesia is getting higher, particularly in big cities like Surabaya, the second largest city in Indonesia. Aesthetic considerations become a major factor in choosing a car. With the rapidly growing amount of cars, the number of car repair services also increased. This is because the car owners always wants their car to be perfect. Therefore, whenever there is minor or major accident, the car owners will try to restore the condition of their car to its initial condition. Yuspeed is one of car repair shops in the city of Surabaya. A companys revenue is influenced by a lot of things, one of which is the presence of good interior design. With a well planned interior design in YuSpeed, it is expected to provide a good repair services, and also makes visitors feel pampered and comfortable.